2014
DOI: 10.5397/cise.2014.17.4.175
|View full text |Cite
|
Sign up to set email alerts
|

Coracoclavicular Ligament Suture Augmentation with Anatomical Locking Plate Fixation for Distal Clavicle Fracture

Abstract: Background: For Neer type IIB fracture of distal clavicle with coracoclavicular ligament injury, various surgical treatments have been used in literatures. However, there was no consensus on the optimal treatment. The aim of this study is to report the clinical and radiological results of open reduction and internal fixation of unstable distal clavicle fracture and suture augmentation of disrupted coracoclavicular ligament. Methods: A prospective study was performed in 23 patients with Neer type IIB distal cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Some authors reported additional CC ligament fixation with suture anchor in locking plate fixation with good clinical outcomes. 11,16) Recent biomechanical studies also demonstrated that CC fixation provides improvement of stability in locking plate fixation for type II distal clavicle fracture. 15) However, since this method requires more soft tissue dissection for CC fixation, it increases the possibility of nonunion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors reported additional CC ligament fixation with suture anchor in locking plate fixation with good clinical outcomes. 11,16) Recent biomechanical studies also demonstrated that CC fixation provides improvement of stability in locking plate fixation for type II distal clavicle fracture. 15) However, since this method requires more soft tissue dissection for CC fixation, it increases the possibility of nonunion.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors therefore suggested modified combined techniques, such as tension band with transacromial K-wire, and CC ligament suture augmentation with locking plate, with satisfactory clinical results. [14][15][16] However, the optimal treatment for type II fracture is still controversial.…”
Section: Introductionmentioning
confidence: 99%